Healthy eating perceptions of mothers and caregivers of children in South Africa - Suzan M. Mokone; Mashudu Manafe; Lindiwe J. Ncube (AOSIS, 2023)
Background: The perceptions of mothers and caregivers of children attending early childhood development (ECD) centres play a very critical role in promoting healthy eating habits in children and impact long-term health consequences. Food preferences that are developed during childhood continue into adolescence and adulthood and are difficult to change. Aim: The aim of the study was to assess the perception of mothers and caregivers of children attending ECD centres regarding healthy eating practices. Setting: The study was conducted in ECD centres in Gauteng, North West and Limpopo. Methods: A quantitative descriptive design was used to collect data among 290 respondents using a structured, researcher-administered questionnaire. Results: The findings indicated that the majority (77%) of respondents did not believe that choosing a healthy diet is a matter of knowing foods that are good and bad for health. The majority (59%) of respondents believed that the food they eat and drinks are healthy and see no need to make changes. Conclusion: The study findings showed that the majority of respondents lack awareness about choosing healthy diets. Furthermore, the current dietary patterns of respondents and their children will remain the same as long as the mothers and caregivers feel that the food they eat is healthy. Contribution: The findings of the study contribute to the appropriate measures of educating mothers and caregivers in offering healthy diets to children at home and in early childhood centres.